Cross-talk between protein synthesis, energy metabolism and autophagy in cancer. (February 2018) - Lindqvist, Lisa M; Tandoc, Kristofferson; Topisirovic, Ivan; Furic, Luc
Highlights: Protein synthesis is one of the most energy consuming processes in the cell. Nutrient availability modulates growth signaling and protein synthesis rates. Autophagy is a survival mechanism providing metabolic substrates during stress. Nutrient sensing, protein synthesis and autophagy are coordinated via mTORC1. Abstract : Translation is a pivotal step in the regulation of gene expression as well as one of the most energy consuming processes in the cell. Dysregulation of translation caused by the aberrant function of upstream signaling pathways and/or perturbations in the expression or function of components of the translation machinery is frequent in cancer. In this review, we discuss emerging findings that highlight hitherto unappreciated aspects of signaling to the translation apparatus with the particular focus on emerging connections between protein synthesis, autophagy and energy homeostasis in cancer.